Deep brain stimulation of the subthalamic nucleus in obsessive–compulsives disorders: long-term follow-up of an open, prospective, observational cohort. Issue 12 (8th October 2020) - Chabardes, Stephan; Krack, Paul; Piallat, Brigitte; Bougerol, Thierry; Seigneuret, Eric; Yelnik, Jerome; Fernandez Vidal, Sara; David, Olivier; Mallet, Luc; Benabid, Alim-Louis; Polosan, Mircea
Abstract : Background: Obsessive–compulsive disorder (OCD) is a major cause of disability in western country and responsible for severe impairment of quality of life. About 10% of patients present with severe OCD symptoms and require innovative treatment such as deep brain stimulation (DBS). Among possible targets, the non-motor subthalamic nucleus (STN) is a key node of the basal ganglia circuitry, strongly connected to limbic cortical areas known to be involved in OCD. Method: We analysed, in a prospective, observational, monocentric, open label cohort, the effect of chronic non-motor STN-DBS in 19 patients with treatment-resistant OCD consecutively operated in a single centre. Severity of OCD was evaluated using the Yale and Brown Obsessive–Compulsive Scale (YBOCS). YBOCS scores at 6, 12 and 24 months postoperatively were compared with baseline. Responders were defined by >35% improvement of YBOCS scores. Global Assessment Functioning (GAF) scale was used to evaluate the impact of improvement. Results: At a 24-month follow-up, the mean YBOCS score improved by 53.4% from 33.3±3.5 to 15.8±9.1 (95% CI 11.2–20.4; p<0.0001). Fourteen out of 19 patients were considered as responders, 5 out of 19 being improved over 75% and 10 out of 19 over 50%. GAF scale improved by 92% from 34.1±3.9 to 66.4±18.8 (95% CI 56.7–76.1; p=0.0003). The most frequent adverse events consisted of transient DBS-induced hypomania and anxiety. Conclusion: Chronic DBS of the non-motor STN is an effective and relatively safe procedure to treat severe OCD resistant to conventional management.